Melioidosis in goats at a single Australian farm was caused by multiple diverse lineages of Burkholderia pseudomallei present in soil. - Joseph D Busch; Mirjam Kaestli; Mark Mayo; Chandler C Roe; Adam J Vazquez; Jodie Low Choy; Glenda Harrington; Suresh Benedict; Nathan E Stone; Christopher J Allender; Richard A Bowen; Paul Keim; et al. (PLoS Neglected Tropical Diseases, 2024)
Background Burkholderia pseudomallei, causative agent of melioidosis, is a One Health concern as it is acquired directly from soil and water and causes disease in humans and agricultural and wild animals. We examined B. pseudomallei in soil and goats at a single farm in the Northern Territory of Australia where >30 goats acquired melioidosis over nine years. Methodology/principal findings We cultured 45 B. pseudomallei isolates from 35 goats and sampled soil in and around goat enclosures to isolate and detect B. pseudomallei and evaluate characteristics associated with its occurrence; 33 soil isolates were obtained from 1993-1994 and 116 in 2006. Ninety-two goat and soil isolates were sequenced; mice were challenged with six soil isolates to evaluate virulence. Sampling depth and total N/organic C correlated with B. pseudomallei presence. Twelve sequence types (STs) were identified. Most goat infections (74%) were ST617, some with high similarity to 2006 soil isolates, suggesting ST617 was successful at persisting in soil and infecting goats. ST260 and ST266 isolates were highly virulent in mice but other isolates produced low/intermediate virulence; three of these were ST326 isolates, the most common soil ST in 2006. Thus, virulent and non-virulent lineages can co-occur locally. Three genes associated with virulence were present in ST260 and ST266, absent in most ST326 isolates, and present or variably present in ST617. Conclusions/significance Agricultural animals can influence B. pseudomallei abundance and diversity in local environments. This effect may persist, as B. pseudomallei was detected more often from soil collected inside and adjacent to goat enclosures years after most goats were removed. Following goat removal, the low virulence ST326, which was not isolated from soil when goats were present, became the predominant ST in soil by 2006. Although multiple diverse lineages of B. pseudomallei may exist in a given location, some may infect mammals more efficiently than others.